Resource Allocation Effects of Price Reactions to Disclosures* - Dye, Ronald A.; Sridhar, S. (Contemporary Accounting Research, 2002)
Abstract Capital market participants collectively may possess information about the valuation implications of a firm's change in strategy not known by the management of the firm proposing the change. We ask whether a firm's management can exploit the capital market's information in deciding either whether to proceed with a contemplated strategy change or whether to continue with a previously initiated strategy change. In the case of a proposed strategy change, we show that managers can extract the capital market's information by announcing a potential new strategy, and then conditioning the decision to implement the new strategy on the size of the market's price reaction to the announcement. Under this arrangement, we show that a necessary condition to implement all and only positive net present value strategy changes is that managers proceed to implement some strategies that garner negative price reactions upon their announcement. In the case of deciding whether to continue with a previously implemented strategy change, we show that it may be optimal for the firm to predicate its abandonment/continuation decision on the magnitude of the costs it has already incurred. Thus, what looks like “sunk‐cost” behavior may in fact be optimal. Both demonstrations show that, in addition to performing their usual role of anticipating future cash flows generated by a manager's actions, capital market prices can also be used to direct a manager's actions. It follows that, in contrast to the usual depiction of the information flows between capital markets and firms as being one way — from firms to the capital markets — information also flows from capital markets to firms.